Clues About Conducting Research With Children: Microethical Moments in an Interviewing Experience - Freitas, Bárbara; Gaudenzi, Paula; Costa Andrada, Bárbara (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
This article reflects on the process of constructing and conducting interviews with children, emphasizing the microethical moments that arise, explored through two theoretical-methodological “clues.” It examines the ethical challenges and tensions inherent in research shaped by adult-centric and developmentalist logics. We present strategies to address these limitations, including recognizing children as active subjects, using a registry of informed agreement in video format, engaging in joint negotiation, employing chat-interviews, and encouraging the use of drawing. Through an “epistemological vigilance,” the study advocates for a balance between protecting children and ensuring their meaningful participation, contributing to ethical practices in research involving children.